(untitled) (Journal of Plant Disease Sciences, 2021)
A lab experiment was conducted to evaluate different fungicides and antagonists against Rhizoctonia bataticola and Fusarium solani causing root rot in Plantago ovata. Among the entire systemic and non-systemic combination product, Carbendazim (0.1%), Propiconazole (0.1%), Thiram (0.3%) and Carbendazim + Mancozeb (0.2%) gave cent percent inhibition of Rhizoctonia bataticola and Fusarium solani. In general, Thiophanate M 0.2% and Chlorothalonil 0.2% were moderate to least efficient against Rhizoctonia bataticola and Fusarium solani. In case of antagonists Trichoderma viride and Trichoderma harzianum gave maximum inhibition as compared to Pseudomonas fluorescence.